A Detection Method for Transmission Line Insulators Based on an Improved FCM Algorithm - BoWen Wang; Quan Gu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
An improved segmentation Fuzzy C-Means algorithm (FCM) is proposed for the image recognition of transmission line insulators. In this paper, the improved Wiener filter algorithm is firstly used to filtrate and recover image in pre-processing. Then, the insulator image is segmented based on the improved algorithm FCM. Finally, the contour of insulator is labelled by using connected component labelling algorithm. Experimental results have shown that the improved Wiener filtering algorithm may effectively filter and recover the images; furthermore, the improved FCM image segmentation algorithm may accurately segment insulators from the image.